Temperament, brain structure and problematic video gaming in adolescence: a six-year longitudinal study - Mürner-Lavanchy, Ines M.; Sele, Silvano; Simmons, Julian; Lubman, Dan I.; Whittle, Sarah; Allen, Nicholas B.; Kaess, Michael (Journal of behavioral addictions, 2025)
Background Growing concerns regarding problematic gaming highlight the need for prospective longitudinal research to explore potential targets for prevention. Markers that can be observed during early adolescence, prior to the establishment of problematic behaviors, may be particularly informative. Two potential predictors of interest that have been shown to reflect important developmental and psychopathological processes are temperament and brain structure, which respectively provide self-reported and objective markers of individual differences. Methods Temperament (n = 245) and brain volume (n = 154) were assessed at 11-13 years, and problematic video gaming (dimensional gaming addiction score; n = 130) at 17-19 years, in adolescents selected from a community sample to maximize variation in temperament. Associations between temperament and problematic video gaming were tested. Further models explored whether brain volume, and interactions between brain volume and temperament explained additional variance in predicting problematic video gaming. Results Negative affectivity (b = 2.94 [95% CI 0.32, 5.57]), as well as male gender (b = −6.61 [−10.64, −2.59]), were associated with later problematic video gaming. Also, lower effortful control in male participants was associated with higher odds for problematic video gaming in later adolescence (b = 4.32 [CI 0.24, 8.39]). Exploratory analyses showed modest evidence for an interaction between effortful control and amygdala volume in predicting problematic video gaming. Conclusions This six-year prospective longitudinal study, confirms associations between negative affectivity and effortful control and later problematic video gaming. Further, higher effortful control might have a protective role in individuals with larger amygdalae, who are vulnerable to mental health disorders, such as video gaming addiction.
Gesehen am 10.02.2026